Prospective Evaluation of the Safety and Efficacy of Thermomechanical Fractional Injury for Perioral Rhytides - Wang, Jordan V; Bajaj, Shirin; Steuer, Alexa; Orbuch, David; Geronemus, Roy G (Dermatologic surgery, 2023)
Perioral rhytides can be treated with laser and energy-based devices. More recently, a novel fractional thermomechanical skin rejuvenation system was developed to cause controlled thermal injury through direct heat transfer. A prospective clinical trial evaluated the safety and efficacy of a thermomechanical fractional injury device (Tixel 2, Novoxel, Netanya, Israel) for perioral rhytides. Subjects with moderate-to-severe perioral rhytides were enrolled and underwent 4 monthly treatments. Twenty-three subjects were enrolled and completed all study visits. Mean age was 62.5 years, and 100.0% were women. Fitzpatrick Skin Types I-IV were included. For Fitzpatrick Wrinkle Classification System (FWCS), mean baseline score was 6.9. Per investigator, there was a mean 1.9-grade improvement in FWCS at 3-month follow-up ( p < .0001). At 3-month follow-up, 8.7% (n = 2) of subjects had a 3-grade improvement, 69.6% (n = 16) had a 2-grade improvement, and 21.7% (n = 5) had a 1-grade improvement. For physician Global Aesthetics Improvement Scale at 3-month follow-up, 69.6% (n = 16) had 76% to 100% improvement, 13.0% (n = 3) had 51% to 75% improvement, and 17.4% (n = 4) had 26% to 50% improvement. There were no severe adverse events, and subjects experienced minimal pain. A novel device using thermomechanical fractional injury was demonstrated to be safe and effective in the treatment of perioral rhytides.